(untitled) (Pharmacy Practice, 2017)
Background: Patient information may assist in promoting shared decision-making, however it is imperative that the information presented is comprehensible and acceptable to the target audience. Objective: This study sought to explore the acceptability and comprehensibility of the ‘Medicines in Scotland: What’s the right treatment for you?’ factsheet to the general public. Methods: Qualitative semi-structured telephone interviews were conducted with members of the public. An interview schedule was developed to explore the acceptability and comprehensibility of the factsheet. Participants were recruited by a researcher who distributed information packs to attendees (n=70) of four community pharmacies. Interviews, (12-24 minutes duration), were audio recorded, transcribed verbatim and analysed using a framework approach. Results: Nineteen participants returned a consent form (27.1%), twelve were interviewed. Six themes were identified: formatting of the factsheet and interpretation; prior health knowledge and the factsheet; information contained in the factsheet; impact of the factsheet on behaviour; uses for the factsheet; and revisions to the factsheet. Conclusions: The factsheet was generally perceived as helpful and comprehensive. It was highlighted that reading the leaflet may generate new knowledge and may have a positive impact on behaviour.